2021
DOI: 10.1186/s12957-021-02463-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of three micro-RNA gene polymorphisms with the risk of cervical cancer: a meta-analysis and systematic review

Abstract: Objective Regulation of single nucleotide polymorphisms (SNP) in micro-RNA (miRNA) on the host cells may be one of the most important factors influencing the occurrence of cervical cancer based on the prevalence of HPV infection and the development of cervical cancer. In order to explore the contribution of miRNA polymorphism to the occurrence and development of cervical cancer, we conducted an analytical study. Methods We selected the polymorphism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, patients with CC or CG genotypes of rs2910164 were more susceptible to the other cancers. At the same time, three large meta-analyses found that the CC genotype was associated with a decreased risk of cervical, hepatocellular, and prostate cancer [ 123 , 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with CC or CG genotypes of rs2910164 were more susceptible to the other cancers. At the same time, three large meta-analyses found that the CC genotype was associated with a decreased risk of cervical, hepatocellular, and prostate cancer [ 123 , 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was conducted using STATA 15.1 (StataCorp LP) 23 was used to analyze the data. OR with 95% confidence intervals (95%CI) were utilized for analyzing the risk factors of cardiovascular and cerebrovascular disease subtypes.…”
Section: Methodsmentioning
confidence: 99%
“…STATA 15.1 [14] was used to analyze the data. OR (95% Cl) was used to analyze the risk factors of subtype of cardiovascular and cerebrovascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…[13] 2.5. Data synthesis and statistical analysis STATA 15.1 [14] was used to analyze the data. OR (95% Cl) was used to analyze the risk factors of subtype of cardiovascular and [15] Cohort study Any stroke 7…”
Section: Literature Quality Assessmentmentioning
confidence: 99%